Major Diseases Affecting Rubber and Its Control Measures Adopted by Small Growers of Vaikom Taluk - Sreedharan A P (Department of Plantation Crops and Spices, College of Agriculture, 1992)
The major diseases affecting rubber in Vaikom taluk were powdery mildew, pink and abnormal leaf fall. Powdery mildew was more serious and infected about 99 per cent of the holdings surveyed. Dusting of sulphur at the time of refoliation can control the spread of the disease. Use of the chemical at the recommended dose was not adopted by the growers. This can be the main reason for the spread of the disease. Infection of pink disease was not so serious in the surveyed area. About 10.7 per cent of the trees were seen infected. Detection of the diseses at the early stages of infection and treatment of the trees was more important in the control of pink. It was obvious that the farmers knowledge in plant protection techniques were poor. No grower was seen adopting thiride treatment against pink though it was recommended as effective to Bordeaux paste. Lack of awareness of growers can be the main reason. Abnormal leaf fall was the least serious among the three diseases. The clone RRII 105 showed average tolerance to the disease and that can be the reason for the mild infection of the disease in the surveyed units. The study showed extension activities among the growers were highly inadequate. RRII 105 being the main clone, the leaf retention during monsoon was satisfactory even without prophylactic spraying. Therefore, prophylactic spraying was not seen as generally accepted practice among the growers of Vaikom taluk. Powdery mildew disease was very common in the surveyed units. But, many of the growers were neglecting it. All clones were seen infected with the disease. Repeated dusting of sulphur mixed with talc can control the infection effectively if sprayed at bud break. Four to six rounds of dusting should be done for the control of the disease. Extra weeding in plantation become necessary due to leaf fall and hence maintenance cost is higher. Unavailability of plant protection equipments was another difficulty faced by the growers. To overcome these difficulties disease tolerant clones may be planted in future. Moreover, the extension methods are to be strengthened to educate the growers about the diseases and its timely control.